Vitellogenin Receptor (VgR) Mediates Oocyte Maturation and Ovarian Development in the Pacific White Shrimp (Litopenaeus vannamei) - Ruan, Yao; Wong, Nai-Kei; Zhang, Xin; Zhu, Chunhua; Wu, Xiaofen; Ren, Chunhua; Luo, Peng; Jiang, Xiao; Ji, Jiatai; Wu, Xugan; Hu, Chaoqun; Chen, Ting (Frontiers in Physiology, 2020)
Oocyte maturation and ovarian development are sequentially coordinated events critical to reproduction. In the ovaries of adult oviparous animals such as birds, bony fish, insects and crustaceans, vitellogenin receptor (VgR) is a plasma membrane receptor that specifically mediates vitellogenin (Vg) transport into oocytes. Accumulation of Vg drives sexual maturation of the female crustaceans by acting as a pivotal regulator of nutritional accumulation within oocytes, a process known as vitellogenesis. However, the mechanisms by which VgR mediates vitellogenesis are still not fully understood. In this study, we first identified a unique VgR (Lv-VgR) and characterized its genomic organization and protein structural domains in Litopenaeus vannamei, a predominant cultured shrimp species worldwide. This newly identified Lv-VgR phylogenetically forms a group with VgRs from other crustacean species within the arthropod cluster. Duplicated LBD/EGFD regions are found exclusively among arthropod VgRs but not in paralogs from vertebrates and nematodes. In terms of expression patterns, Lv-VgR transcripts are specifically expressed in ovaries of female shrimps, which increases progressively during ovarian development, and rapid declines toward embryonic development. The cellular and subcellular locations were For analyzed by in situ hybridization and immunofluorescence, respectively. The Lv-VgR mRNA was found to be expressed in the oocytes in the ovaries, and Lv-VgR protein was found to localize in the cell membrane of maturing oocytes while accumulation of the ligand Vg protein assumed an even cytoplasmic distribution. Silencing of VgR transcript expression by RNAi was effective for stunting ovarian development. This present study has thus provided new insights into the regulatory roles of VgR in crustacean ovarian development.